Al no Incorporarse Medidas Cautelares en el Procedimiento Monitorio establecidas en el COGEP, genera Inseguridad Jurídica - Idrobo Cabrera, David Marcelo (2016)
This thesis entitled "Not Merge Precautionary Measures in the collection proceedings established in the COGEP, generates legal uncertainty"; with the force of the Code General Process The legislature has reformed the system of administration of justice in which the substantiation of the processes carried out by the oral system in which procedural rules enshrine the principles of simplification, uniformity, efficiency , immediacy, speed and procedural economy without shelve the application of the guarantees of due process, establishing the payment procedure that being a process which guarantees the speed of the process, allows a person to request payment of a liquid debt, payable and arrears, but that procedure has not been established to present precautionary measures to ensure compliance with the obligation The actor can not apply for precautionary measures to ensure payment of the debt with which it is intended to claim, as if seen in the executive process. Measures have entirely practical reasons, to be guaranteed in this process fairer and more effective protection of such important today as it is to the credit institution is attempted, in which apart there quickly to be sure a claim on, consisting of the overdue obligation to a liquid amount of money and that the injunction will become an enforceable claim. With these reasons come to substantiate that the lack of predictability and enforceability of a precautionary measure to ensure the payment of a debt 5 they left defenseless to the creditor and what is more does not give possibility of recovery acreency when there is bad faith of the debtor. Thus the payment procedure should be guaranteed legal certainty with application of precautionary measures, being an executive and then process the application of an abbreviated process is the foundation of justice substantive and procedural economy. Through this work of legal research I present the advantages and importance of incorporating precautionary measures in the payment procedure for the benefit of anyone trying to charge a, liquid, due and due and payable particular debt of money, an amount not to exceed fifty unified basic wage worker generally not enforceable record, in order to safeguard the guarantees of due process and justice meet the aspirations of the Ecuadorian people.